(untitled) (Bangladesh Journal of Medical Science, 2009)
Methodology: Effect of pretreatment by crude and n-Hexane extract of Nigella (10mg/kg body wt./day for 21 days) on streptozotocin (STZ, 50 mg/kg body wt. single dose i.p.) administered rats were observed in the present study. Biochemical parameters (Serum glucose, serum TG, serum cholesterol, pancreatic GSH) were compiled together with pancreatic histology. Results: Both the crude and the n-Hexane extract of Nigella pre-treated diabetic rats had demonstrated significant (P<0.001) alleviation from the elevated serum glucose, lowered pancreatic reduced glutathione (P<0.01) and elevated serum TG concentrations (P<0.01). 72% β cells appeared to be damaged by STZ administration, while in the crude and the n-Hexane extract of Nigella pretreated diabetic groups this damage was 31% and 46% respectively, the crude Nigella pretreated group thus appeared to have better amelioration. Conclusions: Further studies are suggested to obtain the protective ingredient from the crude Nigella and to observe its effect upon the above mentioned parameters of diabetic rats in higher doses for prolonged periods. Keywords: Diabetes, Nigella sativa Linn., Streptozotocin. doi: 10.3329/bjms.v8i1.3182 Bangladesh Journal of Medical Science Vol.8 No. 1-2; 2009 5-9